LEGAL PROTECTION FOR HEALTHCARE PROFESSIONALS AND HOSPITALS AGAINST PATIENT’ COMPLAINTS ON SOCIAL MEDIA - Laismono, Stephanie Glory; Putera, Andika Persada; Asmuni, Asmuni (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
In the digital era, social media platforms have evolved into potent communication tools; however, they also present novel obstacles, particularly for healthcare professionals and institutions. The reputation and operations of medical institutions can be substantially influenced by the increase in patient complaints that are shared online.This research was made by using normative legal research type, namely research that focuses on examining legal norms in applicable laws and regulations relating to the subject matter. The aim of this research is to analyze existing complaint services in hospitals as well as legal protection for hospitals and health workers against patient complaints on social media. The result of this research shows that there are still complaint services in hospitals that are not yet well provided, and other factors that cause patients to complain on social media. It also shows that legal protection against defamation in corporations has not been able to serve its purpose well, as well as Indonesian penal law which is oriented towards retributive justice rather than restorative justice.